Peningkatan Keterampilan Berbicara Melalui Media Boneka Tangan Pada Anak Usia 5-6 Tahun - Khusni Alhan; Siti Munawaroh (STAI Publisistik Thawalib Jakarta, 2023)
The aim of the research is to improve the speaking skills of children aged 5 - 6 years using hand puppets at Handayani Caringin Bogor Early Childhood Education. The research was conducted as classroom action research with two cycles on 19 children. Meanwhile, the data analysis technique used is descriptive qualitative by comparing data obtained from initial conditions, cycle I and cycle II with four stages, namely planning action, implementing action, carrying out observation, and reflection. Based on the results of the known data analysis, after the process of using hand puppet media, the child's speaking skills before using hand puppet media received a score of 52.63% with poor criteria and in the first cycle of action, they scored 63.16% with good criteria. In cycle II, the average child's speaking skills after using hand puppets increased by 84.21%.